2012
DOI: 10.1369/0022155411432010
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Localization of WNT Signaling Proteins in a Mouse Model of Distraction Osteogenesis

Abstract: While the surgical procedure of distraction osteogenesis (DO) is very successful in the treatment of orthopedic conditions, its major limitation of slow bone formation in the distracted gap has prompted numerous attempts to understand and accelerate this slow bone formation. Interestingly, WNT/FZD signaling has been identified as a critical pathway in mediating bone formation and regeneration but has not yet been studied in the context of DO. The objective of this study was to determine the spatial and tempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 42 publications
(56 reference statements)
1
13
0
Order By: Relevance
“…The results revealed that the Wnt pathway was more activated at the end of distraction, while the Hippo pathway was more activated during consolidation. These results were consistent with the previous studies, in which Wnt pathways was reported to play important roles in bone formation during DO . However, The studies of whether Fak‐Mapk pathway was activated or not during DO remain unclear.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results revealed that the Wnt pathway was more activated at the end of distraction, while the Hippo pathway was more activated during consolidation. These results were consistent with the previous studies, in which Wnt pathways was reported to play important roles in bone formation during DO . However, The studies of whether Fak‐Mapk pathway was activated or not during DO remain unclear.…”
Section: Discussionsupporting
confidence: 93%
“…Mechanical tension‐stress up‐regulated the entire Bmp pathway during DO . The spatial and temporal localization of Wnt pathway is increased, due to distraction strain, during DO . Meanwhile, some studies found the tension‐stress induced some genes and transcription factors up‐regulated or down‐regulated during DO .…”
Section: Introductionmentioning
confidence: 99%
“…*P , 0.05, ***P , 0.001. through the activation of Wnt10a (30). Wnt10a is known to be up-regulated and essential for bone formation (53)(54)(55). However, Thy1 also has a critical role (56,57).…”
Section: Discussionmentioning
confidence: 99%
“…Severe osteoporosis has also been diagnosed in WNT10A patient, including increased fracture risk and a pathological bone mineral density . Wnt pathway is in close molecular interaction with other crucial pathways, such as BMP and RANKL‐OPG via sclerostin, that are involved in skeletogenesis, bone metabolism and differentiation of osteochondroprogenitors toward an osteoblastic fate . Osteoblastogenesis is based on a specific Wnt level regulation, with reiterated up and down‐regulations of the Wnt pathway, highlighting the importance of the Wnt‐β‐catenin pathway in bone development .…”
Section: Discussionmentioning
confidence: 99%